2020
DOI: 10.17263/jlls.759260
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the needs of postgraduate students: The first step of academic writing courses

Abstract: Academic writing practices constitute central processes through which students learn the conventions of their disciplines to meet the expectations of their academic communities. Therefore, academic writing courses should touch on the specific dimensions of it. One of the most prominent requirements of these courses is to identify the needs of students and implement a program based on the negotiation between the needs of students and the expectations of academic communities. The present study aimed to explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…It elaborated that students had weak command on syntax, lacked knowledge of rhetorical devices, and were untrained in using citation and referencing correctly. A Turkish study found similar results (Yuvayapan & Bilginer, 2020). The study investigated the Master's and PhD students' enrolled in private and public universities.…”
Section: Review Of Literaturementioning
confidence: 65%
“…It elaborated that students had weak command on syntax, lacked knowledge of rhetorical devices, and were untrained in using citation and referencing correctly. A Turkish study found similar results (Yuvayapan & Bilginer, 2020). The study investigated the Master's and PhD students' enrolled in private and public universities.…”
Section: Review Of Literaturementioning
confidence: 65%
“…Additionally, since they can aid in the development of postgraduate students' research skills and confidence, activities like peer-to-peer mentoring and cooperation should be promoted for them. In light of the initial challenges faced by postgraduate students in crafting academic writing, like finding resources and techniques (Singh, 2019), further research has shown that the advanced form of grammar is a significant challenge for postgraduate students, in addition to factors including lack of English competence, difficulties expressing ideas, disordered structure, and plagiarism in writing text (Yuvayapan & Bilginer, 2020). This suggests that the vast majority of graduate students need better grammar proficiency.…”
Section: Introductionmentioning
confidence: 99%
“…For a multitude of reasons, academic writing is challenging for English language learners who are not native speakers (Yuvayapan & Bilginer, 2020). The researcher observed and asked some undergraduate students at the seventh-semester English education study program in FKIP UNTAN about problems they face when writing a proposal.…”
Section: Introduction 1introductionmentioning
confidence: 99%